2020
DOI: 10.1016/j.cpr.2020.101814
|View full text |Cite
|
Sign up to set email alerts
|

The effect of four Immeasurables meditations on depressive symptoms: A systematic review and meta-analysis

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 52 publications
(18 reference statements)
3
30
1
Order By: Relevance
“…The specific procedure is, first, to themselves; second, to loved ones; third, to a neutral person (emotionally neutral to oneself, i.e., neither like nor hate); fourth, to people that disgust them; and, then, to the entire universe. Finally, participants were asked to practice these formal meditation sessions between classes and to use the kindness and love technique in their workplace [51].…”
Section: Lkm Interventionmentioning
confidence: 99%
“…The specific procedure is, first, to themselves; second, to loved ones; third, to a neutral person (emotionally neutral to oneself, i.e., neither like nor hate); fourth, to people that disgust them; and, then, to the entire universe. Finally, participants were asked to practice these formal meditation sessions between classes and to use the kindness and love technique in their workplace [51].…”
Section: Lkm Interventionmentioning
confidence: 99%
“…The article exemplifies the goal of integrating science and practice to refine psychological treatments. Finally, Jing Lv et al ( 2020 ) shared insights from Buddhist meditations that could help to expand traditional western approaches to psychotherapy. Their systematic review and meta-analysis revealed the potential benefit from therapeutic approaches that encourage a focus on four prosocial attitudes.…”
Section: Discussionmentioning
confidence: 99%
“…Considering all this, it is still necessary to propose intervention strategies that can combine the effects of self-regulation factors (self-kindness and mindfulness), for instance the practice of meditation (Lv et al 2020), and factors that facilitate social connectedness (family social support, perception of not being alone and discriminated, and the feeling of belonging), perhaps using online technologies (Liu et al 2020b;Armitage and Nellums 2020), to maintain optimal subjective well-being in people affected by the COVID-19 lockdown. In agreement with other authors (Bansal et al 2020;Koenig 2020), the following are some recommendations to help individuals maintain spiritual, mental, and physical well-being during the COVID-19 pandemic:…”
Section: Discussionmentioning
confidence: 99%